DUKUNGAN SOSIAL ORANG TUA, EFIKASI DIRI, KECEMASAN DALAM MENCARI KERJA DI ERA COVID-19 PADA FRESH GRADUATE UNIVERSITAS X - Frigate Andy Ariyan; Wiwik Sulistiani; Wanda Rahma Syanti (Fakultas Psikologi Universitas Hang Tuah, 2022)
This study aims to determine the relationship between parental social support and self-efficacy with anxiety looking for work in the COVID-19 era in fresh graduates of University X. This study uses a quantitative survey. Subjects 218 fresh graduates. The sampling technique used stratified random sampling. the scale used in this study: the social support scale of parents; self efficacy scale ; anxiety scale. The results of data analysis obtained there is a relationship between self-efficacy and job search anxiety, there is a relationship between social support and student anxiety. A new finding in this study is that parental social support has a positive correlation with job-seeking anxiety in the COVID-19 era, meaning that the higher the social support, the higher the job-seeking anxiety. Shows parental social support, makes fresh graduates feel anxious and afraid to disappoint their parents when they don't get a job and fresh graduates choose to look for work independently so they don't bother their parents.